Tunning pectinase activity under the effects of electric fields in the enhanced clarification of wine must - Queirós, Mariana; Pereira, Guilherme; Leite, Ana Catarina; Leal, Rita; Rodrigues, Rui; Teixeira, José A.; Pereira, Ricardo N. (Frontiers in Sustainable Food Systems, 2023)
Pectinolytic enzymes are of great importance for the clarification process of “Vinho Verde” wine must, contributing to reduce haze development. During the last decade, a growing body of knowledge has been established about electric field effects on activation of important food enzymes. However, the influence of electrical parameters on catalytic activity is enzyme dependent and should be evaluated through a case-by-case basis. This work describes for the first-time the effects of electric field and electric frequency on activity of pectinase (PEC) towards accelerated clarification of “Vinho Verde” must. Moderate electrical fields (MEF) with intensities below 20 V/cm and at electric frequencies ranging from 50 Hz to 20 kHz, were applied at temperatures between 15 ºC and 35 ºC. Enzymatic activity was measured for 25 minutes, and the initial rate of reaction was determined by the coefficient of the linear plot of galacturonic acid (GAL) production as function of time. Results have shown that electrical frequency can increase enzymatic activity depending on temperature conditions; at 20 ºC and electric frequencies of 2 kHz and 20 kHz, enzymatic activity increased up to 40 % and 20 %, respectively, when compared with the control sample (without application of MEF). Temperature dependence was evaluated through Arrhenius equation showing that energy of activation (Ea) can be reduced from 9.2 kJ/mol to 6.6 kJ/mol at sub-optimal temperature for PEC activity, when MEF are applied. Electrical parameters when combined with temperatures below 20 ºC, reduced pectin concentration in “Vinho Verde” wine must up to 42 % of its initial content. This emergent treatment can be integrated in relevant environment conditions bringing an opportunity to increase enzyme efficiency even at a low temperature conditions which favors winemaking process.